Perbandingan Ornamen Surya Majapahit di Museum Trowulan dan Demak: Kajian Motif dan Makna - Riayatul Qiromah; Yulia Masrianingsi Pane (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
The Majapahit Surya Ornament is an ornament in the form of a sun decoration with a circular center and the outermost part forming the rays of the sun. The center is circular and has been divided into eight rooms with one room on the middle side. The Majapahit Surya Ornament is found in the Trowulan Museum and the Great Mosque of Demak. This ornament is a symbol of Hindu-Buddhist cosmology during the Majapahit era, which was adapted into a symbol of monotheism in the Islamic tradition during the Demak Sultanate. This study uses a three-form cultural approach: ideas, activities, and artifacts to analyze the transformation of ornaments in terms of philosophical meaning, social function, and physical form. The results of the study show that in the Trowulan Museum, this ornament is maintained in its original form to symbolize harmony and divine power, while in the Great Mosque of Demak, this ornament has undergone modifications in meaning and technique according to Islamic-Javanese values. This finding reveals the process of harmonious cultural acculturation between Hindu-Buddhist and Islam in Java, while also emphasizing the relevance of the Majapahit Surya ornament as a symbol of the rich and dynamic cultural heritage of the archipelago.